The comparative study between Indonesian blend words and English blend words - Mia Rahmannia; Pratomo Widodo (Department of Applied Linguistics, Graduate School of Universitas Negeri Yogyakarta, 2019)
Generally, blending can be defined as combining two clipped words. Kvetko in Bednarova defines blending as a word formation process similar to shortening combined with merging two different words. There are many types of blending words both in Indonesian and English context. Therefore, the aim of this research is to analyze the comparison between Indonesian blend words and English blend words in terms of its types, its similarities and differences and also how its formed. In this paper the researcher use descriptive qualitative method as the method of the research. The source of the data is taken from some journal articles that relevant with blend words both in Indonesian and English context. The result showed that Indonesian blend words and English blend words not only have similarities in the forming word, but also have their differences that make them unique to each other. The writer hopes that the reader of this article gets more information about both Indonesian and English blend words based on its types and the similarities and the difference between them.